Banco de sementes e seletividade de herbicidas na palma forrageira - Silva, José Alex do Nascimento (2019)
Two experiments were carried out in the experimental area of the Center of Agricultural Sciences of the Federal University of Alagoas (CECA - UFAL), in the city of Rio Largo, Brazil, with the objective of identifying and quantifying the existing species in a forage palm, as well as the herbicide selectivity in the forage palm crop and its effectiveness in weed control. In the first experiment the seed bank and the phytosociological parameters of the weeds in the forage palm crop were evaluated in three depths. The emergence of plants was evaluated every seven days, evaluations occurring up to 160 days after the first emergency. three replications of the soil samples of these depths were carried out at 30, 60 and 90 days after these changes were carried out every time the germination flow could no longer be measured. In the composition of the seed bank were identified 23 plant species distributed in 14 botanical families. It was observed that the seed bank is more active in the first layer of the soil when compared to the other layers. The species E. indica (L.) Gaertn, Phyllanthus tenellus Roxb. and Dactyloctenium aegyptium (L.) Willd were the ones with the highest indices with 62.00; 47.00 and 39.00%. As for the similarity index, it was considered as low, with values of 24.25% of similarity between the layers, in relation to the number of species found. The second experiment evaluated the selectivity of five herbicides as well as the potential of weed control when applied in pre-emergence in forage palm.